EDUKASI ANEMIA PADA PASIEN KANKER PAYUDARA YANG MENJALANI KEMOTERAPI DI KOTA BANDUNG - Oky Octaviani; Desi Kusmawati N; Rere Anggraeni; Raika Graha Septia (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Anemia is a common hematological complication in breast cancer patients undergoing chemotherapy, with a high incidence during the course of therapy. This community service article aims to describe the implementation of anemia education in breast cancer patients undergoing chemotherapy in Bandung and assess its effect on changes in participants' knowledge levels. The evaluation results showed a significant increase in participants' knowledge scores after attending the counseling session. The average total knowledge score increased from 44.52 on the pre-test to 83.52 on the post-test, indicating a better understanding of the general aspects of anemia, clinical symptoms, causes related to chemotherapy, and methods of prevention and management. The implementation of such counseling is highly recommended on an ongoing basis in the context of health services to strengthen patients' ability to cope with the side effects of chemotherapy.